The Edinburgh companion to fin de siècle literature, culture and the arts - Guy, Josephine M., 1963- (Edinburgh : Edinburgh University Press, 2018)
"The late nineteenth-century fin de siècle has proved an enduringly fascinating moment in literary and cultural history. It is associated with the emergence of intriguing figures -- such as the 'new woman' and 'uranian'; with contradictory impulses -- of decadence and decay on the one hand, and of experiment and renewal, on the other; as well as with unprecedented intercultural exchange, especially between Britain and France. The 22 newly-commissioned essays collected here re-examine some of the key concepts taken to define the fin de siècle, while also introducing hitherto overlooked cultural phenomena into the frame, such as the importance of humanitarianism. The impact of recent research in material culture is explored, particularly how the history of the book and the history of performance culture is changing our understanding of this period. A wide range of cultural activities is discussed -- from participation in avant-garde theatre to interior decoration and from the writing of poetry to political and religious activism. Together, the essays provide new scholarly insights into British fin de siècle and enrich our understanding of this complex period, while paying particular attention to the importance of regionalism."--
Introduction / Josephine M. Guy -- Part I. Concepts. 1. Decadence and institutions of modernism in the American literary field of the 1910s and 1920s / Kirsten MacLeod -- 2. The matter of form: fin-de-siècle illustrated poetry and the periodical press / Alison Chapman -- 3. Curious ontricacies: some versions of city writing at the fien de siècle / Nick Freeman -- 4. Gothic aesthetics / Andrew Smith -- 5. Catholicism and the fin de siècle / Miriam Elizabeth Burstein -- 6. Secularism and secularisation at the fin de siècle / Sara Lyons -- 7. The claims of kinship: humanitarian ideals at the century's end / John Stokes -- 8. Information in the 1890s: technological, journalistic, imperial, occult / Richard Menke -- Part II. Places. 9. Fin-de-Siècle Scotland / Caroline McCracken-Flesher -- The Irish fin de siècle / Anne Markey -- Providing an ideal home: paternalism and persuasion at Bournville, 1895-1914 / Margaret Ponsonby -- 12. Theatre in the provinces at the fin de siècle: beyond outcast London / Jo Robinson -- 12. 'Truth about Russia': Russia in Britain at the fin de siècle / Anna Vaninskaya -- 14. Aestheticism in Italy: a new sense of place / Stefano Evangelista -- Part III. Identities: female. 15. The 1890's woman / Jad Adams -- 16. When a bestselling author and a West End actress made a spiritualist performance: collaboration, networks and theatre at the fin de siècle / Catherine Hindson -- 17. Intergenerational collaboration and conflict: women's periodicals at the fin de siècle / Alexis Easley -- 18. Lily Montagu and liberal Judaism / Richa Dwor -- 19. American nervousness: motherhood and 'the mental activity of women' in the era of sexual anarchy / Emily Coit -- Part IV. Identities: male. 20. German and British sexual sciences across disciplines at the fin de siècle: 'homosexuals', 'inverts' and 'uranians' / Ina Linge -- 21. The Anglo-African adventure novel in the 1890s / Gerald Monsman -- 22. The fin-de-siècle detectives: 'but my job don't end there' / Caroline Reitz.
Includes bibliographical references and index.
Josephine M. Guy is Professor of Modern Literature at the University of Nottingham. She has published widely on Victorian literature and culture, especially on Oscar Wilde, and is a member of the editorial team of the Oxford English Texts Edition of the Complete Works of Oscar Wilde. She has also published on text-editing and theory, on the history of English as a discipline of knowledge and, more recently, on the scientific study of literature, and the use of psycholinguistic methodologies to investigate literariness.
Print version record.
JSTOR
Keywords: English literature -- 19th century -- History and criticism; English literature -- 20th century -- History and criticism; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature anglaise -- 20e siècle -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM / General; Literature; English literature; Literature; 1800-1999; Literary criticism; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.